Participation of Pesantren in Society 5.0: Building Globally Competitive Skills - Hadiyatullah, Zainur Rofiq; Muna, Ani Roisatul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
Society 5.0 is the age of intelligent societies that participate in training as a place of innovation with modern technology. The aim of this research is to study how trainees participate in Society 5.0 with a focus on human resource development in building traineeships competence in the global world. This research method is library research. (library research). The results of this study revealed that the gymnasium is not only a place for learning, but also a place to form an inclusive character, creating an independent individual with strong ethics and morality. The research also emphasizes important steps to preserve the original character of the trainees, such as instilling a noble morality, applying technology in the training system, ethical digital literacy, and cross-disciplinary collaboration. It helps the coach not only maintain the good tradition, but also create a better new tradition “Al-Muhafadhotu ‘Ala Qodimis Sholih Wal Akhdzu Bil Jadidil Ashlah”. With an innovative approach, the gymnasium becomes a place of education that prepares for the future by blending traditional values and technological advances.